Pengembangan Media Pembelajaran E-Komik dengan Menggunakan Aplikasi Canva pada Materi Wujud Zat dan Perubahannya Kelas IV Sekolah Dasar - Hasibuan, Rusdi Indra; Hader, Antik Estika; Wulandari, Lia (Jurnal Ilmiah Dikdaya, 2024)
The purpose of this study is to develop E-comic learning media using the Canva application on thematerial of the form of matter and changes in grade IV Elementary School that is Valid, Practical, Effective.The development model used in this development is the ADDIE development model. In the development ofADDIE there are five stages of procedures, namely Analysis, Design, Development, Implementation andEvaluation. This study uses the type of research and development (R&D) research. The validity of E-Comicsthat have been carried out by the three validators obtained an average value of 93.4% with a very validcategory. So that the IPAS E-Comics have been said to be valid for use. The practicality of e-Comics that havebeen assessed from the educator response questionnaire obtained a value of 77.8% and The effectiveness of EComics that have been assessed from the results of student learning tests obtained a value with a completecategory of 91.67% categorized as very effective because they can facilitate educators in the learning process.